Psychosocial Effects of Corona Measures on Patients With Dementia, Mild Cognitive Impairment and Subjective Cognitive Decline - van Maurik, Ingrid S.; Bakker, Els D.; van den Buuse, Susanne; Gillissen, Freek; van de Beek, Marleen; Lemstra, Evelien; Mank, Arenda; van den Bosch, Karlijn A.; van Leeuwenstijn, Mardou; Bouwman, Femke H.; Scheltens, Philip; van der Flier, Wiesje M. (Frontiers in Psychiatry, 2020)
Background: The recent COVID-19 pandemic is not only a major healthcare problem in itself, but also poses enormous social challenges. Though nursing homes increasingly receive attention, the majority of people with cognitive decline and dementia live at home. We aimed to explore the psychosocial effects of corona measures in memory clinic (pre-)dementia patients and their caregivers. Methods: Between April 28th 2020 and July 13th 2020, n=389 patients of Alzheimer center Amsterdam (n=121 symptomatic (MCI, dementia; age=68±6, 33%F, MMSE=23±5), n=268 non-symptomatic (subjective cognitive complaints (SCD), age=63±8, 40%F, MMSE=29±1) completed a survey on psychosocial effects of the corona measures. Questions related to social isolation, worries for faster cognitive decline, behavioral problems and discontinuation of care. In addition, n=147 caregivers of symptomatic patients completed a similar survey with additional questions on caregiver burden. Results: Social isolation was experienced by n=42 (35%) symptomatic and n=67 (25%) non-symptomatic patients. Worries for faster cognitive decline were commonly reported by symptomatic patients (n=44 (44%)) and caregivers (n=73 (53%)), but also by as substantial subgroup of non-symptomatic patients (n=27 (14%)). Both patients (n=56 (46%) symptomatic, n=102 (38%) non-symptomatic) and caregivers (n=72 (48%)) frequently reported an increase in psychological symptom. More than three quarter of caregivers (n=111 (76%)) reported an increase in patients’ behavioral problems. Two third of patients (n=129 (66%); n=58 (75%) symptomatic, n=71 (61%) non-symptomatic) reported that care was discontinued. The majority of caregivers reported higher caregiver burden (n=69 (56%)), and n=43 (29%) reported that they needed more support. Red flags for higher caregiver burden were discontinued care (OR=3.3[1.3-7.9]), psychological (OR=4.0[1.6-9.9]) and behavioral (OR=3.0[1.0-9.0]) problems. Social isolation (OR=3.2[1.2-8.1]) and psychological symptoms (OR=8.1[2.8-23.7]) were determinants for worries for faster cognitive decline. Conclusion: Not only symptomatic patients, but also non-symptomatic patients express significant worries for faster cognitive decline and psychological symptoms. Moreover, we identified patients who are at risk of adverse outcomes of the corona measures, i.e. discontinued care, social isolation, psychological and behavioral problems. This underlines the need for health care professionals to provide ways to warrant the continuation of care and support (informal) networks surrounding patients and caregivers to mitigate the higher risk of negative psychosocial effects.